Mapping the Free Energy of Lithium Solvation in the Protic Ionic Liquid Ethylammonuim Nitrate: A Metadynamics Study. Issue 15 (10th July 2017) - Kachmar, Ali; Carignano, Marcelo; Laino, Teodoro; Iannuzzi, Marcella; Hutter, Jürg
Abstract: Understanding lithium solvation and transport in ionic liquids is important due to their possible application in electrochemical devices. Using first‐principles simulations aided by a metadynamics approach we study the free‐energy landscape for lithium ions at infinite dilution in ethylammonium nitrate, a protic ionic liquid. We analyze the local structure of the liquid around the lithium cation and obtain a quantitative picture in agreement with experimental findings. Our simulations show that the lowest two free energy minima correspond to conformations with the lithium ion being solvated either by three or four nitrate ions with a transition barrier between them of 0.2 eV. Other less probable conformations having different solvation pattern are also investigated. Abstract : Free the ion : The free‐energy surface for lithium solvation in ethylammonium nitrate is estimated from the metadynamics potential acting in the reduced phase space of two selected collective variables. Simulations show that the lowest two free energy minima correspond to conformations with the lithium ion being solvated either by three or four nitrate ions with a transition barrier between them of 0.2 eV. The black dots mark the minimum energy pathway (MEP).